Glycemic Control Status After Percutaneous Coronary Intervention and Long-Term Clinical Outcomes in Patients With Type 2 Diabetes Mellitus. (April 2017) - Hwang, Jin Kyung; Lee, Seung Hwa; Song, Young Bin; Ahn, Joonghyun; Carriere, Keumhee; Jang, Mi Ja; Park, Taek Kyu; Choi, Seung-Hyuk; Yang, Jeong Hoon; Choi, Jin-Ho; Lee, Sang Hoon; Gwon, Hyeon-Cheol; et al.
Abstract : Background—: Data on the association between glycemic control after percutaneous coronary intervention and clinical outcomes are limited and controversial in diabetic patients. Methods and Results—: We studied 980 patients with type 2 diabetes mellitus undergoing percutaneous coronary intervention using drug-eluting stents. Based on 2-year glycosylated hemoglobin A (HbA1c) levels, we divided patients into 2 groups of HbA1c<7.0 (n=489) and HbA1c≥7.0 (n=491). Propensity score–matched analysis was performed in 322 pairs. The primary outcome was major adverse cardiac and cerebrovascular events (MACCE), defined as a composite of cardiac death, myocardial infarction, repeat revascularization, or stroke. Median follow-up duration was 5.4 years. The 7-year incidence of MACCE was lower in the HbA1c<7.0 group than in the HbA1c≥7.0 group (26.9% versus 40.3%; adjusted hazard ratio, 0.75; 95% confidence interval, 0.57–0.98; P =0.03). After propensity score matching, the 7-year incidence of MACCE was still lower in the HbA1c<7.0 group than in the HbA1c≥7.0 group (27.5% versus 37.4%; hazard ratio, 0.71; 95% confidence interval, 0.52–0.97; P =0.03), mainly because of a reduction in repeat revascularization (19.9% versus 29.5%; hazard ratio, 0.66; 95% confidence interval, 0.47–0.93; P =0.02). In subgroup analyses, the benefit of glycemic control for MACCE was more prominent in patients with residual SYNTAX score (Synergy Between PCI With Taxus and Cardiac Surgery) >4 than in those with the residual SYNTAX score ⩽4 ( P interaction =0.004). Conclusions—: HbA1c<7.0 measured 2 years after percutaneous coronary intervention was associated with a reduced rate of MACCE. Our data suggest that high HbA1c levels 2 years after percutaneous coronary intervention may identify a population at increased risk of adverse events, especially repeat revascularization. Abstract : Supplemental Digital Content is available in the text.